State "Salafism" in Malaysia: development of the "Sunnah" reform ideology in Perlis, Malaysia - Malik, Maszlee (Bangladesh Institute of Islamic Thought (BIIT), 2017)
Since the arrival of Islam in Tanah Melayu or Malaya, traditionalist scholars have dominated the Islamic discourse through their close relations with the rulers (Sultans). Their domination over the religious authorities and the Islamic educational institutions has shaped the state-version of Islam in Malaysia. However, in Perlis, the northernmost state in Malaysia, Middle-Eastern graduate reformists, also known as Kaum Muda were already preaching the earliest version of Salafism in the early 20th century. They found political patronage from the rulers of the state, hence, imposing their version of Islamic teachings as the prevailing Islamic discourse of the state, which is also known until today as the ‘Sunnah Perlis’ teachings. The widely presumptuous masses and researchers point that the dominating influence of the reform agenda or ‘Sunnah’ in the state of Perlis is due to the state authority’s patronage based on historical facts that the ‘Sunnah’ itself first emerged in Perlis in the early 20th century with the blessings of the ruler.